'Material contribution' after Williams v The Bermuda Hospitals Board. (6th July 2018) - Bailey, SH
Abstract: This paper reviews the status of the principle that a claimant can demonstrate a causal link between the defendant's wrongful act or omission and his or her damage by establishing that the act/omission made a 'material contribution' to the damage. This principle has been reviewed, in the context of cumulative causes that cannot be 'compartmentalised', by the Privy Council in Williams v The Bermuda Hospitals Board . There, the Privy Council regarded the cases of Bonnington Castings v Wardlaw (leaving aside the point as to the divisibility of the disease pneumoconiosis), Bailey v Ministry of Defence and Williams itself as essentially similar to each other. They were to be regarded as cases where the court was entitled to conclude that it was the totality of the exposures/delay in question that caused the ultimate harm. As regards Bailey, this was said in terms not to involve any modification of the but-for test; presumably the same holds good for Bonnington Castings and Williams itself. So orthodoxy appears to be preserved/restored. But is that so?